Normative Foundations of Islamic Education Based on Qur'anic Pedagogical Values - Salma Raudya Rachma; Cecep Anwar; Hilma Fauzia Ulfa; Shofa Fauziyah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
Education in Islam is inherently value-driven and aims at holistic human Development grounded in moral and spiritual consciousness. This study aims to formulate Qur'anic pedagogical values as normative foundations for Islamic education by examining their epistemological, methodological, and character-based dimensions. Employing a qualitative, normative–interpretative approach, the study analyzes selected Qur'anic verses alongside classical and contemporary tafsir, drawing on authoritative exegetes and scholarly literature through a systematic thematic analysis. The findings demonstrate that Islamic education is founded on a theocentric epistemology emphasizing literacy, knowledge transmission, and lifelong learning; an ethical and dialogical pedagogy rooted in wisdom and non-coercive communication; and a character education model centered on family-based moral formation. These results indicate that Qur'anic pedagogy offers an integrated and operational educational framework rather than abstract moral ideals. The study contributes a coherent normative model that bridges classical Qur'anic interpretation with contemporary academic discourse. It recommends the systematic integration of Qur'anic pedagogical values into curriculum design, instructional strategies, and teacher formation to strengthen the moral and philosophical coherence of Islamic education.